Activité antimicrobienne des actinobacteries isolés de la rhizosphère de Daucus sahariensis Murb. - DAHMANI, BOUZID, Warda Fatiha (Université de m'sila, 2017)
The constant evolution of the bacterial resistance in antibiotics and the emergence of new infectious diseases justify the urgency to arrange new antimicrobial molecules. In this study we tested the antimicrobial activity of actinomycetes isolated form asoil of plant Daucus sahariensisbreM , appropriated of the region Boussaada à M’sila, arid zone to semi-arid situated in the north-east of Algeria,The antimicrobial activity was estimated by the technique of stries croisées against feve bacteria Bacillus subtilis ATCC 6633, Kelbseuillapheumoniae ATCC 532,Enterococusfaccalis ATCC 2035, E. coli ATCC 25922, Staphylococcus aureus and filamentous fungi phytophtora (phytopathogenic), and Candida albicans ATCC10231 yeast. The three actinobacter MSBA1, MSBA2 and MSBA5 isolate have shown activity against at for tests bacteria.The larger zones of inhibition were observed with MSBA5 possess a strong activity against at least one of the microorganisms-tests. These isolates can be a potential agent producing of many bioactive molecules, in particular the antibiotics of interest biotechnology and pharmacology
Keywords: Isolation, Actinobacter, rhizosphere Soil, antimicrobial Activity.